Parallel Blade-Vortex Interaction Modelling for Helicopter Rotor Noise Control Synthesis. Issue 7 (December 2014) - Modini, Sara; Graziani, Giorgio; Bernardini, Giovanni; Gennaretti, Massimo
The present work deals with a methodology for the alleviation of loads and corresponding emitted noise generated by blade-vortex interaction (BVI) phenomena occurring on helicopter main rotors in low-speed, descent flight. It consists of a multi-cyclic, optimal control approach driving higher harmonic blade pitch actuation. First, for the specific flight condition to be examined, the BVI phenomena are simulated as equivalent two-dimensional, multi-vortex, parallel BVI problems and then a local controller methodology is applied for the efficient identification of the closed-loop control algorithm. In order to assess the capability of the proposed control approach to alleviate rotor blade loads and emitted noise, the results of a numerical investigation concerning a realistic helicopter main rotor in descent flight are presented and discussed.